Peningkatan Aspek Bahasa Anak Usia Dini Melalui Model Storytelling di TK Garuda 005 Sawah - Vany Aprilia; Lusi Marleni; Citra Ayu (Jurnal Pendidikan Tuntas, 2024)
This study is motivated by the low language in group B children at Garuda 005 Sawah Kindergarten, North Kampar District, Kampar Regency. The purpose of this class action research is to improve children's language aspects through the storytelling model in early childhood at Garuda 005 Sawah Kindergarten. This research was carried out in 2 cycles, in each cycle there were 2 meetings, which consisted of the following activities: planning, implementation, observation, reflection. The research time was carried out from May 22 to May 30. Population and samples in this study in group B which amounted to 18 children, 9 boys and 9 girls. The data analysis technique in this research is quantitative descriptive technique. Data collection techniques were carried out by observation and documentation. The results showed that there was an increase in children's language aspects starting from 6% preaction, in cycle I 56%, when carried out in cycle II to 83%. It can be concluded that through the storytelling model can improve children's language aspects in group B at Garuda 005 Sawah Kindergarten said to be successful by reaching 83% in the very well developed category.